The Study of Sindhi Folk-tales Portrayal in Shah Abdul Latif Bhittai’s Poetry - Kaneez Ume Farwa (International Research Journal of Education and Innovation, 2020)
Research is a scientific work on best using the space for a pleasing and aesthetic environment of any building that could have a spiritual or social connection to generations. It is achieving the best successful strategy to effectively pursue interior space, matching of colors best representations of colors to human thinking and behaviors. Similarly, the poetic art, words, expressions are best presentations of human emotions and realities. It is highly needed to understand the connection of beautiful words, cultural stories with the scientific approach of various disciples including the architecture. The Poetry of Hazrat Shah Abdul Latif Bhittai is very fascinating and powerful to understand such scientific concepts. There is a combination of colors, unique sculpture, the practical experiences of women familiarly circulated as “Seven Queens”. The scientific study of interior designing with the connection of such cultural stories in poetic form would open up the new chapters for further researches and innovations. The present research discovers the concepts of Sindhi folk-tales and including the best portrayals of folk-tales as highlighted in poetry of Shah Abdul Latif Bhittai.